PERKAWINAN SESAMA JENIS DAN HAK ASASI MANUSIA: PENERAPAN PRINSIP EQUALITY DALAM PUTUSAN OBERGEFELL, et.al. v. HODGES, USA SERTA ANALISIS MENGENAI PERKAWINAN SESAMA JENIS DI INDONESIA - Holy K.M. Kalangit; Heru Susetyo (University Of Bengkulu Law Journal, 2020)
AbstractThe ‘rights’ and ‘equality’ arguments have been widely used in the last couple of years by the same-sex marriage supporters in claiming the legalization of same-sex marriage. The principle of equality in same-sex marriage legalization claims is closely related with the concept of human rights on the ground that the principle of equality is considered as one of the most important principles in the said concept. The decision of the Supreme Court of the United States of America in Obergefell et al. v. Hodges, Director, Ohio Department of Health is the latest decision concerning the legalization of same-sex marriage that changes radically the legality of same-sex marriage in the United States and may affect other nations. This research analyzes the said Decision, specifically on the application of the principle of equality. This research also analyzes the same-sex marriage issue in Indonesia from the perspective of universality and cultural relativism of human rights. The conclusion of this research is that the principle of equality in the Decision of the Supreme Court of the United States of America was not correctly applied and therefore it cannot be used in the same-sex marriage claims. And in Indonesia, it can be concluded that from the perspective of universality and cultural relativism of human rights, same-sex marriage cannot be legalized.Keywords: human, rights, same-sex, marriage, equality, universality, cultural, relativism.